Evaluation of Fed-Batch Fermentation for Production of Polyhydroxybutyrate With a Banana Pulp Juice Substrate From an Agro Industrial By-Product - Arias-Roblero, Mónica; Mora-Villalobos, Vanny; Velazquez-Carrillo, Carmela (Frontiers in Sustainable Food Systems, 2021)
Pollution resulting from the persistence of plastics in the environment has driven the development of substitutes for these materials through fermentation processes using agro-industrial wastes. Polyhydroxybutyrate (PHB) is a rapidly biodegradable material with chemical and mechanical properties comparable to those of some petroleum-derived plastics. PHB accumulates intracellularly as an energy reserve in a wide variety of microorganisms exposed to nutritionally imbalanced media. The objective of this study was to evaluate the use of a banana waste product as a carbon source for PHB production. PHB was extracted by acid methanolysis and detected by gas chromatography-mass spectrometry. Twenty bacterial strains with potential for PHB production were evaluated by in vitro fermentation in a culture broth containing fructose as the carbon source and limited nitrogen. A 22 central composite rotational design was applied to optimize the concentrations of banana juice and ammonium chloride needed to maximize the PHB-producing biomass concentration. The process was then carried out in a 3L fed-batch fermentation system that included an initial stage of biomass growth. Banana juice was used as the carbon source and fructose pulses were added to maintain the test sugar concentrations of 30, 40 and 50 g/L. The control strain, Cupriavidus necator (ATCC 17699), produced 2,816 g/L of PHB, while productivity of the most promising isolate, C. necator (CR-12), was 0,495 g/L. Maximum biomass production was obtained using 5 % banana juice and 2 g/L ammonium chloride. PHB production was not detected in fed-batch fermentations supplemented with 30 or 40 g/L of fructose, while the mean PHB production in fermentations with 50 g/L of fructose was 1,3 g/L.